Hidrolisis Ampas Biji Sorgum dengan Microwave untuk Produksi Gula Pereduksi sebagai Bahan Baku Bioetanol - Sefrinus M. D. Kolo; Eduardus Edi (Saintek Lahan Kering, 2018)
Sorghum is a cereal plant that can grow in various environmental conditions so that it is potential to be developed, especially on dry climate marginal land in Indonesia. Sweet sorghum has great potential to be used as raw material for ethanol besides sugar cane. Cultivation of sweet sorghum has shifted from food and feed raw materials to industrial raw materials, both small and large scale. This study aims to obtain reducing sugar levels as raw material for bioethanol through hydrolysis using a microwave. As much as 10 grams of sorghum powder is suspended with dilute H2SO4 solution of 0.1 N, 0.3 N and 0.5 N as much as 250 mL and then heated using microwave irradiation at a temperature of 200 oC for 20 and 40 minutes. The liquid fraction produced by hydrolysis was analyzed by reducing sugar content with the DNS method using a UV-Vis spectrophotometer. The results obtained showed that the optimum hydrolysis conditions using microwave were achieved at concentrations of H2SO4 0.5 N at 200 oC and hydrolysis time at 40 minutes. Reducing sugar content of 42.71 mg / L. The sugar content rises by 19.95% compared to the hydrolysis time of 20 minutes.